Socio Economic Profile of Goat Farmers in Southern Region of India - , N. Kumaravelu; , A. Rajadurai; , D. Divyalakshmi; , J. Shilpa Shree (Archives of Current Research International, 2025)
The goat is one of the smallest domesticated ruminants, contributing to the production of milk after cattle and buffaloes, and can survive on shrubs, trees, and desert scrubs and even thrive under minimum housing inputs. Goat farming in southern India is largely traditional, with low input and low output systems. The socio-economic profile of goat farmers is a critical factor in determining the productivity and sustainability of goat farming. This study seeks to analyze the socio-economic profile of goat farmers in southern India, focusing on parameters such as demographics, land use, income patterns, access to services, and market participation. For this study, three states such as Tamil Nadu, Kerala, and Maharashtra were selected. From each study location, 30 farms with not less than 10 adult goat holdings were selected. The primary data collection was carried out through face-to-face interviews. Of the 180 respondents included in the study, 75.60% of respondents are male, followed by 24.4% of respondents are female. The findings showed that 39.4% of respondents had attended the Secondary level, 31.7% of respondents had not attended the secondary level, 22.2% of respondents had attended the primary level, and only, 4.44% of the respondents studied college and above. The majority of the goat farmers (45.60%) had been involved a decade in goat keeping followed by 11-20 years (37.80%), 21-30 years (15.00%) and above 31 years (2.80%) respectively. The socio-economic profile of goat farmers reveals their strengths—resilience, indigenous knowledge, and community-based rearing systems—as well as their constraints—limited resources, institutional exclusion and market vulnerability. This study contributes to that broader understanding and provides a roadmap for strengthening the goat farming sector in a way that is inclusive, sustainable, and empowering.